A Study Of The Effect Of Olive (Olea Europaea) Stem Methanol Extract As An Antibacterial Against Staphylococcus Aureus Bacteria - Raharja, Davin; Dewi, Bernadette DN; Tjipto, Bambang W (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction: Herbal medicine is starting to become an alternative to treating various diseases. Based on proven research, olive plants (Olea europaea) have the potential to inhibit the growth of bacteria that causes infections. Drugs to treat bacterial infections are antibiotics, and high exposure to antibiotics could increase the possibility of resistance. At the end of the 1940s, it was shown that 28% of the Staphylococcus aureus (S. aureus) bacteria were already resistant to penicillin. Several classes of antibiotics have been created to deal with S. aureus infections. Still, these bacteria show their unique ability to respond quickly to some of the new antibiotics in producing resistance effect. That is why we need another alternative to overcome infections caused by these bacteria. Aim: The purpose of this study is to know the effect of olive (Olea europaea) stem methanol extract as an antibacterial against Staphylococcus aureus bacteria. Methods: This study uses an experimental study with the broth microdilution method, using extract concentrations of 200-51.200 µg/mL. Minimum Inhibitory Concentration (MIC) values were obtained from the results of spectrophotometer reading, and Minimum Bactericidal Concentration (MBC) was obtained from the results of streaking on agar media. Result: In this study the MIC value at a concentration of 200-51.200 µg/mL could not be evaluated because it showed no linear lines, and the MBC value was not found. But there was a reduction in the number of colonies at a concentration of 51.200 µg/mL by approximately 50%. Conclusion: Methanol extract of olive stems proved to have no antibacterial effect against Staphylococcus aureus bacteria at concentrations of 200-51.200 µg/mL.